Differential Virus-Specific IFN-Gamma Producing T Cell Responses to Marek’s Disease Virus in Chickens With B19 and B21 MHC Haplotypes - Boodhoo, Nitish; Behboudi, Shahriar (Frontiers in Immunology, 2022)
Marek’s disease virus (MDV), the etiologic agent for Marek’s disease (MD), causes a deadly lymphoproliferative disease in chickens. Causes of the well-documented association between genetically defined lines of chicken and resistance to MD remain unknown. Here, the frequencies of IFN-gamma producing pp38 and MEQ-specific T cell responses were determined in line N (B21 haplotype; MD-resistant) and line P2a (B19 haplotype, MD-susceptible) chickens after infection with vaccine and/or virulent (RB1B) strains of MDV using both standard ex vivo and cultured chIFN-gamma ELISPOT assays. Notably, MDV infection of the vaccinated MD-resistant chickens induced higher frequencies of IFN-gamma producing MDV-specific T cell responses using ex vivo ELISPOT assay. A greater T cell response was also detected after MDV infection of the naïve MD-resistant chickens using ex vivo ELISPOT assay. Remarkably, unlike in the resistant chickens, vaccination did not induce or boost MEQ-specific effector T cells in the susceptible chickens. Taken together, our results revealed that there is a direct association between the magnitude of T cell responses to PP38 and MEQ of MDV antigens and resistance to the disease.